Geochemistry and Genesis of Oil and Gas Seeps in the Junggar Basin, NW China: Implications for Hybrid Petroleum Systems - Jingkun Zhang; Jian Cao; Yan Wang; Jun Li; Guang Hu; Ni Zhou; Tianming Shi (Geofluids)
The Junggar Basin of NW China is representative in containing oil and gas seeps worldwide as there are a wide variety of oil and gas seeps over a large area. However, the genesis of these seeps remains poorly known, limiting the understanding of their implications for petroluem geology and hydrocarbon exploration. Here, we investigate 26 samples of oil and gas seeps from nine outcrops within five areas along the margins of the Junggar Basin to determine the geochemical characteristics of the hydrocarbons, constrain their genesis, and discuss future exploration strategies. Results indicate one type of gas seeps and five types of oil seeps. The gas seeps are derived from low-maturity Jurassic source rocks and occur in the Wusu and Dushanzi areas in the western segment of the southern basin. Type 1 oil seeps, sourced from lower Permian rocks (P1f), occur on the northwestern margin. Type 2 oil seeps, derived from middle Permian source rocks (P2l/P2p), occur on the eastern segment of the southern margin and eastern margin of the Junggar Basin. Type 3 oil seeps, with Jurassic source rocks, occur in the Qigu area in the middle segment of the southern basin. Type 4 oil seeps, with Cretaceous source rocks, occur in the Anjihai and Huoerguosi areas within the middle segment of the southern basin. Type 5 oil seeps mainly have Paleogene source rocks with a minor contribution from Jurassic rocks and occur in the Wusu and Dushanzi areas in the western segment of the southern basin with the single-type gas seeps. These results indicate the presence of lacustrine hybrid petroleum systems within the Junggar Basin with complex oil and gas sources and migration-accumulation. Six potential areas along the basin margin were proposed for exploration in the future.